Development of a clinical protocol for detection of cervical cancer precursor lesions - Deise Maria Do Nascimento Sousa; Ana Carolina Maria Araújo Chagas; Camila Teixeira Moreira Vasconcelos; Airton Tetelbom Stein; Mônica Oliveira Batista Oriá (Revista Latino-Americana de Enfermagem, 2018)
ABSTRACT Objective: to develop and validate the content of a clinical protocol aimed at prevention of cervical cancer in primary care. Method: technological research according to the steps: (1) submission of the project to the research ethics committee; (2) bibliographic survey; (3) elaboration of the clinical protocol; and (4) content validation. In the third step, the information was collected through bibliographic research and gynecology specialists were consulted. For the final step, four judges were selected to evaluate the clinical protocol according to AGREE 2. Domains that reached the minimum level of agreement of 75% in the scores were considered validated. Results: the scores obtained in each domain of the instrument were as follows: domain 1 (scope and purpose) = 87.5%; domain 2 (stakeholder involvement) = 83.3%; domain 3 (development rigor) = 79.7%; domain 4 (clarity of presentation) = 76.3%; domain 5 (applicability) = 78.1%; and domain 6 (editorial independence) = 85.4. Conclusion: the clinical protocol proved to be a validated material with scores above the minimum required. The protocol obtained positive recommendations with modifications and went through adjustments in order to make it more effective.